Tour of historical sites in Natal and Zululand : Natal Educational Activities Association (Historia, 2021)
One of the problems which face teachers of history, and to which the solution is most elusive is that of making history interesting, alive and of immediate importance. However one strives to make the presenta-tion of past deeds, ideas, ideals and problems vivid by a dramatic and forceful presentation, the visual element is still lacking. Map.s, charts, pictures, diagrams and descriptions conjure up an imperfect impression of the reality which one wishes to convey. Some element is missing, how- ever skilled the teacher may be. The answer to this problem would SOON be obvious to a chemistry teacher in a similar predicament: the actua.l process described must be repeated with apparatus used in the original experiment. This is obviously not possible in teaching history, but one may go part of the way towards solving the problem by a partial recon-struction of the past: the scene of some historic deed may be visited or the remains of a culture may be studied. In this way the pupil's imagina-tion may be stimulated so that these things will move into focus and animate his knowledge of history derived from books and verbal narration.
Keywords: Natal; Historical sites; Teaching history; Zululand; Tour; Natal Educational Activities Association; History as subject